EFEKTIFITAS PEMBERIAN AROMA TERAPI LAVENDER TERHADAP PENURUNAN NYERI PERSALINAN DI RSHB KOTA BATAM - A.Hafidz, Rahmawati; Heroyanto, Heroyanto; J. Margiyanti, Norma (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Childbirth pain can cause stress that causes excessive release of hormones such as catecholamines and steroids. Childbirth pain can also, causing the onset of hyperventilation so that oxygen needs increase, blood pressure increases, and decreased intestinal motility and vesika urinaria. Pain management in persalianan can be done by pharmacological and nonpharmacological methods. Non-pharmacological methods can also increase satisfaction during childbirth, since the mother can control her feelings and strength. One type of terpi aroma that can be utilized for pain reduction is lavender oil. The main ingredients of lavender flowers are linalyl acetate and linalool (C10H18O). Linalool is the main active content that plays a role in the relaxing effect. The purpose of this study is to determine the effectiveness of Lavender Aroma Therapy Against Decreased Childbirth Pain. This research uses quantitative research design with case control research method. This research was conducted at Harapan Bunda Hospital Batam with a total of 66 respondents. The results found that there were differences in pain levels between the group given the aroma of lavender therapy and the group that was not given the aroma of lavender therapy. It is recommended that every health worker can use non pharmacological methods of lavender aroma therapy to reduce pain during childbirth.